Achieving the strength-ductility balance of boron nitride nanosheets/Al composite by designing the synergistic transition interface and intragranular reinforcement distribution. (November 2022) - Ma, Lishi; Zhang, Xiang; Pu, Bowen; Zhao, Dongdong; He, Chunnian; Zhao, Naiqin
Abstract: The distribution state of reinforcement in matrix plays a significant role in affecting the strength-ductility relationship in metal matrix composites. Restricted by the great distinction in geometrical size, intrinsic properties and the poor wettability, the discontinuous reinforcement particulates are commonly accustomed to being distributed at grain boundaries and thus being stuck in the disadvanced stress concentration near the interface. Herein, we report a strategy to realize the special in-situ intragranular AlN nanoparticles together with a well-bonded intergranular two-dimensional transition nanosheets/metal interface structure in boron nitride nanosheets (BNNSs)/Al system through the integrated segmented ball milling (SBM) and reaction sintering route. It is revealed that the BNNSs-AlN-Al transition interface can effectively alleviate the stress partitioning at the interface in the initial stage of plastic deformation. And the coherent intragranular AlN/Al interface benefits to a strong interfacial bonding and leading to the multiplication of intragranular dislocations during the subsequent deformation. The combined effect improved the deformation uniformity of the composites and delayed the crack propagation. As a result, a high strength-ductility balance was achieved in BNNSs/Al composites. The present work may provide a new protocol for achieving high strength-ductility synergy for metal matrix composites. Graphical abstract: Image 1